2017
DOI: 10.1038/nrmicro.2017.61
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas predators: understanding and exploiting phage–host interactions

Abstract: Species in the genus Pseudomonas thrive in a diverse set of ecological niches and include crucial pathogens, such as the human pathogen Pseudomonas aeruginosa and the plant pathogen Pseudomonas syringae. The bacteriophages that infect Pseudomonas spp. mirror the widespread and diverse nature of their hosts. Therefore, Pseudomonas spp. and their phages are an ideal system to study the molecular mechanisms that govern virus-host interactions. Furthermore, phages are principal catalysts of host evolution and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 170 publications
(185 reference statements)
1
159
0
4
Order By: Relevance
“…Phages represent the most abundant biological entities on earth, and are key ecological drivers of microbial community dynamics, activity and adaptation; thereby impacting environmental nutrient cycles, agricultural output, and human and animal health [1][2][3][4][5][6][7][8]. Despite nearly a century of pioneering molecular work, the mechanistic insights into phage specificity for a given host, infection pathways, and the breadth of bacterial responses to different phages have largely focused on a handful of individual bacterium-phage systems [9][10][11][12][13]. Bacterial sensitivity/resistance to phages is typically characterized using phenotypic methods such as cross-infection patterns against a panel of phages [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or by whole-genome sequencing of phage-resistant mutants [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Phages represent the most abundant biological entities on earth, and are key ecological drivers of microbial community dynamics, activity and adaptation; thereby impacting environmental nutrient cycles, agricultural output, and human and animal health [1][2][3][4][5][6][7][8]. Despite nearly a century of pioneering molecular work, the mechanistic insights into phage specificity for a given host, infection pathways, and the breadth of bacterial responses to different phages have largely focused on a handful of individual bacterium-phage systems [9][10][11][12][13]. Bacterial sensitivity/resistance to phages is typically characterized using phenotypic methods such as cross-infection patterns against a panel of phages [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or by whole-genome sequencing of phage-resistant mutants [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments to remove these prophage-like sequences revealed remarkable changes in host physiological traits (Zeng et al, 2016;Argov et al, 2017;De Smet et al, 2017). These records of interactions between the genomic parasite and its host may encode valuable ecological information (see Box 3).…”
Section: A Symbio-centric Ecological Speciation Frameworkmentioning
confidence: 99%
“…A common theme by which phages affect host physiology to benefit phage progeny development is through the modulation or inhibition of bacterial cellular processes (1,2). Previous studies (6)(7)(8)(9) revealed that SPO1 infection results in the remodelling of several host processes by six (Gp38, Gp39, Gp40, Gp44, Gp50 and Gp51) of the twenty-six genes encoded by the host takeover module.…”
Section: Discussionmentioning
confidence: 99%
“…Much like eukaryotic and archaeal viruses, which derail the host's cellular processes to facilitate viral replication, phages have evolved complex strategies to acquire their bacterial hosts. In order to successfully infect and replicate in the bacterial cell, many phages encode proteins that specifically interfere with essential biological processes of the host bacterium, including transcription, translation, DNA replication and cell division (1). Phage proteins that interfere with host processes are typically small in size (on average ~160 amino acid residues) and are usually produced at high levels early in the infection cycle (2).…”
Section: /Bodymentioning
confidence: 99%